2020
DOI: 10.3233/ch-200818
|View full text |Cite
|
Sign up to set email alerts
|

The impact of moderate Aortic Valve Disease in patients undergoing MitraClip for severe MR

Abstract: BACKGROUND: High surgical risk patients presenting with severe mitral valve regurgitation (MR) and concomitant aortic valve disease are frequently a challenge for the interdisciplinary heart team meeting. If open-heart surgery for severe MR is performed, aortic stenosis (AS) or regurgitation (AR) is corrected during the same procedure if at least moderate severity of AS or AR has been confirmed. In patients with prohibitive surgical risk, optimal management strategies in the light of available transcatheter in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Whether TR contributes alone to dismal outcome or only in conjunction with RV dysfunction is controversial and has to be further assessed. In addition, a recent study reported about the negative impact of moderate aortic regurgitation on survival [ Table 4] [75] . Prior intervention of the aortic valve has repeatedly been reported as a negative prognostic factor for patients treated with TMVr [42,57,76] .…”
Section: Composed Pmr and Smr Patient Collectivementioning
confidence: 99%
“…Whether TR contributes alone to dismal outcome or only in conjunction with RV dysfunction is controversial and has to be further assessed. In addition, a recent study reported about the negative impact of moderate aortic regurgitation on survival [ Table 4] [75] . Prior intervention of the aortic valve has repeatedly been reported as a negative prognostic factor for patients treated with TMVr [42,57,76] .…”
Section: Composed Pmr and Smr Patient Collectivementioning
confidence: 99%